Hybrid performance measurement of a business process outsourcing - a Malaysian company perspective - Oluyinka, Oludapo Samson; Puteri Fadzline, Tamyez; Cheng, Jack Kie; Freida, Ayodele Ozavize (AIP Publishing, 2017)
It's no longer new that customer perceived value for product and services are now greatly influenced by it's psychological and social advantages. In order to meet up with the increasing operational cost, response time, quality and innovative capabilities many companies turned their fixed operational cost to a variable cost through outsourcing. Hence, the researcher explored different underlying outsourcing theories and infer that these theories are essential to performance improvement. In this study, the researcher evaluates the performance of a business process outsource company by a combination of lean and agile method. To test the hypotheses, we analyze different variability that a business process company faces, how lean and agile have been used in other industry to address such variability and discuss the result using a predictive multiple regression analysis on data collected from companies in Malaysia. The findings from this study revealed that while each method has its own advantage, a business process outsource company could achieve more (up to 87%) increase in performance level by developing a strategy which focuses on a perfect mixture of lean and agile improvement methods. Secondly, this study shows that performance indicator could be better evaluated with non-metrics variables of the agile method. Thirdly, this study also shows that business process outsourcing company could perform better when they concentrate more on strengthening internal process integration of employees.